2019
DOI: 10.1111/vox.12820
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a tool to score donor vein suitability for blood donation

Abstract: Background and Objectives Phlebotomy is a central task for whole blood donation, yet there are no published standards regarding systematic donor vein assessment or the impact of vein quality on successful blood donation. Blood donation failures and related adverse events are highly predictive of donors not returning for future blood donation. A specific blood donation vein scoring tool was assessed to measure donor vein suitability for whole blood collection and investigate the correlation of the donor’s veins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This could potentially be attributed to staff targeting male donors, who they perceive as being more suited to plasmapheresis, or to males reporting a greater number of risky behaviours, such as travel, which prevent donors from giving whole blood. Similarly, Hirani and colleagues [11] found poorer vein suitability for blood donation among females compared to males. Therefore, more males may have been converted to plasma in our cohort based on vein quality.…”
Section: Discussionmentioning
confidence: 97%
“…This could potentially be attributed to staff targeting male donors, who they perceive as being more suited to plasmapheresis, or to males reporting a greater number of risky behaviours, such as travel, which prevent donors from giving whole blood. Similarly, Hirani and colleagues [11] found poorer vein suitability for blood donation among females compared to males. Therefore, more males may have been converted to plasma in our cohort based on vein quality.…”
Section: Discussionmentioning
confidence: 97%
“…13 In the study by Hirani et al mentioned above, it was shown that when experienced staff members were compared with staff having experience of <6 months, the vein score had a good correlation with phlebotomy outcome. 8 It is expected to help in reducing subjectivity with the development of additional training and supporting training materials.…”
Section: Discussionmentioning
confidence: 99%
“…As of date, very little literature is available for assessing vein suitability among apheresis donors, although studies on vein assessment for whole blood donors using vein assessment scoring tools (VST) show better phlebotomy outcome. 8 Ideally, the vein score assessment system would generate a consistent result in assessing vein suitability when used by any phlebotomist, irrespective of their experience or other variables in phlebotomy. This study intends to find out the effectiveness of a VST used and found to be effective in selecting whole blood donors in reducing the difficulty in identifying good quality veins for the plateletpheresis procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of individual WAHVAC variables ( n = 17, 85.0%; and n = 16, 80.0%, respectively) also had excellent agreement for interrater and test–retest reliability (adjusted κ statistics >0.75). The WAHVAC has an advantage over other instruments that assess peripheral intravenous cannulation complexity for the insertion of catheters (Civetta et al, 2019; Hirani et al, 2019; Pagnutti et al, 2016; Van Loon et al, 2019) as the variables on the instrument are specific to HD VA.…”
Section: Discussionmentioning
confidence: 99%
“…Instruments that assess access complexity for the related but different scenario of peripheral intravenous catheter insertion are common (Civetta et al, 2019; Hirani et al, 2019; Pagnutti et al, 2016; Van Loon et al, 2019). There is currently no “gold standard” for grading the complexity of HD VA and no published instrument to assess HD VA complexity.…”
Section: Literature Reviewmentioning
confidence: 99%